Holistic sport psychology: Incorporating the holistic growth of the athlete within a consultant's professional philosophy - Friesen, Andrew (University of Ottawa (Canada), 2008)
The present qualitative study aimed to explore the integration of holistic athlete development into sport psychology service delivery. Using the framework of professional philosophy from Poczwardowski, Sherman, and Ravizza (2004), five holistic sport psychology consultants were interviewed about their service delivery. Five athletes were also interviewed about their experiences working with these consultants. Deductive and inductive content analyses (Patton, 2002) were used to examine the data collected. Results offer three perspectives as to the meaning of holistic sport psychology: (a) Managing environmental effects from non-sport domains to the athlete's performance; (b) developing the individual beyond the athlete; and (c) recognizing the dynamic relationship between an athlete's mental, emotional, physiological states, and their behaviour. Themes from the consultants' beliefs, values, theoretical paradigms to behaviour change, models of practice, roles, operating standards, intervention goals, and intervention techniques and methods are also presented and discussed within the context of various service delivery topics.
Keywords: Health Sciences, Recreation.